Proximal promoter elements of the human zeta-globin gene confer embryonic-specific expression on a linked reporter gene in transgenic mice. - Pondel, M D (1996)
We have investigated the transcriptional regulation of the human embryonic zeta-globin gene promoter. First, we examined the effect that deletion of sequences 5' to zeta-globin's CCAAT box have on zeta-promoter activity in erythroid cell lines. Deletions of sequences between -116 and -556 (cap = 0) had little effect while further deletion to -84 reduced zeta-promoter activity by only 2-3-fold in both transiently and stably transfected erythroid cells. Constructs containing 67, 84 and 556 bp of zeta-globin 5' flanking region linked to a beta-galactosidase reporter gene (lacZ) and hypersensitive site -40 (HS-40) of the human alpha-globin gene cluster were then employed for the generation of transgenic mice. LacZ expression from all constructs, including a 67 bp zeta-globin promoter, was erythroid-specific and most active between 8.5 and 10.5 days post-fertilisation. By 16.5 days gestation, lacZ expression dropped 40-100-fold. These results suggest that embryonic-specific activation of the human zeta-globin promoter is conferred by a 67 bp zeta-promoter fragment containing only a CCAAT and TATA box.